Alkali-Metal-Templated Self-Assembly of Nickel(II) [12-MC-3] Metallacoronates Based on Bis(pyrazol-1-yl)acetato Ligands - Beyer, Andreas; von Gernler, Marc; Pflock, Stephan; Türkoglu, Gazi; Müller, Lisa; Zahl, Achim; Gieb, Klaus; Müller, Paul; Drewello, Thomas; Burzlaff, Nicolai (Chemistry - A European Journal, 2018)
Keywords: Metallacrowns; Nickel; Acetyl acetonate; Template synthesis; Tripodal ligands

Selective stabilization of HIF-1α in renal tubular cells by 2-oxoglutarate analogues - Schley, Gunnar; Klanke, Bernd; Schödel, Johannes; Kroening, Sven; Türkoglu, Gazi; Beyer, Andreas; Hagos, Yohannes; Amann, Kerstin Ute; Burckhardt, Birgitta C.; Burzlaff, Nicolai; Eckardt, Kai-Uwe; Willam, Carsten (American Journal of Pathology, 2012)
The role of proximal versus distal tubular injury in the pathogenesis of acute kidney injury (AKI) is debatable. Inhibition of prolyl hydroxylases that regulate the degradation of hypoxia-inducible transcription factors (HIFs) is a promising therapeutic approach to optimize energy preservation under hypoxia and has successfully been applied to protect kidney structure and function in AKI models. Presently used prolyl hydroxylase inhibitors are lipophilic 2-oxoglutarate analogues (2OGAs) that are widely taken up in cells of most organs. Given the selective expression of organic anion transporters (OATs) in renal proximal tubular cells, we hypothesized that hydrophilic 2OGAs can specifically target proximal tubular cells. We found that cellular hydrophilic 2OGAs uptake depended on OATs and largely confined to the kidney, where it resulted in activation of HIF target genes only in proximal tubular cells. When applied in ischemia-reperfusion experiments, systemically active 2OGA preserved kidney structure and function, but OAT1-transported 2OGA was not protective, suggesting that HIF stabilization in distal tubular rather than proximal tubular cells and/or nontubular cells mediates protective effects. This study provides proof of concept for selective drug targeting of proximal tubular cells on the basis of specific transporters, gives insights into the role of different nephron segments in AKI pathophysiology, and may offer options for long-term HIF stabilization in proximal tubules without confounding effects of erythropoietin induction in peritubular cells and unwarranted extrarenal effects. © 2012 American Society for Investigative Pathology.